THE MEANING OF INDEPENDENCE FOR GENERATION Z AUDITORS: A PHENOMENOLOGICAL STUDY OF JUNIOR AUDITORS IN PUBLIC ACCOUNTING FIRM - Ardhani, Lutfi; Ahmed, Essia Ries; Alabdullah, Tariq Tawfeeq Yousif (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study explores how Generation Z junior auditors interpret independence in the context of audit practices in Public Accounting Firms (KAP), particularly in East Java, using an interpretive phenomenological approach. Given changing generational values, commercial pressures from KAPs, and ongoing independence violations, this study seeks to fill a gap in understanding the lived experiences of young auditors in negotiating independence as a fundamental ethical principle. Data were collected through in-depth semi-structured interviews with Generation Z junior auditors in several KAPs and were analyzed thematically to uncover the construction of meaning, shaping factors, and response strategies to conflicts between personal aspirations and structural demands. The findings indicate that independence is interpreted not only as formal adherence to standards and codes of ethics, but also as part of moral identity, self-integrity, and an "inner brake" in dealing with client pressure, firm culture, and commercial targets, shaped by a combination of Gen Z's distinctive values, the socialization process in KAPs, and concrete experiences of ethical dilemmas in the field. Gen Z junior auditors respond to the tension between personal values and organizational demands through various coping strategies, ranging from communication adjustments and seeking support from role models to self-reflection and, in extreme cases, changing accounting firms or leaving the profession when they feel independence is no longer aligned with their personal values. Practically, the research results confirm that strengthening independence requires the design of ethics policies and coaching systems that are more dialogical, generation-sensitive, and based on real cases, so that the process of internalizing independence values ​​does not stop at normative slogans, but is realized in the daily audit decisions of Generation Z junior auditors.